CHARACTERISTICS OF SELECTED FACTORS OF SPLENOMEGALY IN DOMESTIC DOGS - Локес, П. І.; Кравченко, С. О. (Scientific Progress & Innovations, 2015)
Results of scientific research for the study of etiological factors, clinical symptoms, laboratory values and changes of ultrasonographic features for splenomegaly in dogs are presented in this work. We established that the etiological factors of splenomegaly is pathologies which is accompanied by blood circulation disorders, haematopoiesis and a pigmentary metabolism. Clinical symptoms of splenomegaly is increasing the size of spleen, as determined by palpation and ultrasonography. The basic provisions for implementing splenomegaly classification in animals with determination of an isolated and systemic form are stated.